The Role of Diverting Stoma After an Ultra-low Anterior Resection for Rectal Cancer - Seo, Seok In (The Korean Society of Coloproctology, 2013)
PURPOSE: A diverting stoma is known to reduce the consequences of distal anastomotic failure following colorectal surgery. The aim of this study was to evaluate the efficacy of a diverting stoma after an ultra-low anterior resection (uLAR) for rectal cancer. METHODS: Between 2000 and 2007, 836 patients who underwent an uLAR were divided into two groups, depending on the fecal diversion: 246 received fecal diversion, and 590 had no diversion. Patient- and disease-related variables were compared between the two groups. RESULTS: Thirty-two of the 836 patients (3.8%) had immediate anastomosis-related complications and required reoperation. Anastomosis leakage comprised 72% of the complications (23/32). The overall immediate complication rate was significantly lower in patients with a diverting stoma (0.8%, 2/246) compared to those without a diverting stoma (5.1%, 30/590; P = 0.005). The fecal diversion group had lower tumor location, lower anastomosis level, and more preoperative chemo-radiation therapy (P < 0.001). In total, 12% of patients in the diverting stoma group had complications either in making or reversing the stoma (30/246). CONCLUSION: The diverting stoma decreased the rate of immediate anastomosis-related complications. However, the rate of complications associated with the diverting stoma was non-negligible, so strict criteria should be applied when deciding whether to use a diverting stoma.